The Current Management of Cardiac Tumours: a Comprehensive Literature Review - Joshi, Mihika (Braz J Cardiovasc Surg, 2020)
OBJECTIVE: To understand the current evidence and guidelines behind the appropriate management of cardiac tumours. METHODS: A comprehensive electronic literature search has been performed in major databases - PubMed, Embase, Scopus, Ovid, and Google Scholar. All articles that discussed all different forms of cardiac tumours, their clinical presentation, diagnosis, and management methods have been critically appraised in this narrative review. RESULTS: All relevant studies have been summarized in appropriate sections within our review. Cardiac tumours are rare but can be catastrophic and life-threatening if not identified and managed on timely manner. Utilization of all the available imaging methods can be of equivocal importance, relevant to each cardiac tumour. Surgical excision is the ultimate treatment method, however histopathological results can guide the adjunct treatment. CONCLUSION: Early detection of cardiac tumours has significant effect on planning the method of intervention. Technological advancements and increased availability of imaging modalities have enabled earlier and more accurate detection of these tumours. Novel medical therapies, recommendations for screening, and operative techniques have all contributed to overall improving knowledge of these tumours and ultimately patient outcomes.